Використання розрахункового методу в ГІС режиму ґрунтової вологи - Коваленко, Володимир Васильович; Kovalenko, Vlаdіmyr Vasiljevich; Довганенко, Денис Олександрович; Dovganenko, Denis Aleksandrovich (ФГБОУ ВО Волгоградський ДАУ, 2018)
Представлені методологія інтеграції агрогідрометеорологічного методу розрахунку запасів вологи (АГММРВ) в геоінформаційну систему режиму ґрунтової вологи (ГІС РГВ) і результати апробації ГІС РГВ в умовах дослідного поля інституту зернових культур НААН України. The methodology of integrating the agrohydrometeorological method for calculating moisture reserves (AGMMRV) in the geoinformation system of soil moisture regime (GIS RPV) and the results of approbation of the GIS of RPW in the experimental field of the Institute of Grain Crops of the National Academy of Sciences of Ukraine are presented.
Use of the calculation method in the GIS regime of soil moisture
Keywords: агротехнології; agrotechnology; геоінформаційні системи; geoinformation systems; режим грунтової вологи; soil moisture regime